The Use of Expressive Acts in The Movie "Air Mata di Ujung Sajadah" and Its Relevance as Teaching Materials for Drama Texts in Grade XI SMA - Purwaningsih, Hanifa Chyntya Intan; Prabawa, Andi Haris (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The purpose of this research is (1) to identify the forms of expressive speech acts in the movie Air Mata di Ujung Sajadah found by researchers in pragmatics studies and (2) its relevance in Indonesian language learning on drama text material. This research uses qualitative method with descriptive approach. The data used in this research is primary data obtained from direct data collection efforts by identifying the sentences contained in the movie. The data collection technique in this research uses listening and note-taking techniques. The analysis method in this research uses pragmatic pairing method. The findings obtained are (1) there are 30 data of expressive speech acts, consisting of 7 data of expressive speech acts of praising, 6 data of expressive speech acts of sadness, 4 data of expressive speech acts of gratitude, 4 data of expressive speech acts of surprise, 3 data of expressive speech acts of congratulating, 3 data of expressive speech acts of expecting, 3 data of expressive speech acts of apologizing; and (2) expressive speech acts in the film Air Mata di Ujung Sajadah are relevant to the drama text for class XI.